Chemical Constituents of Herbertus dicramus, Three New Herbertene Type Sesquiterpenes - Bal, Selma (Asian Journal of Chemistry, 2010)
Three new herbertane-type sesquiterpenes, 2-hydroxyherbertene, methyl-2-hydroxyherberten- 12-oate and methyl-2-methoxyherberten-12-oate have been isolatd from the extract of Herbertus dicramus. Two known compounds, (-)-α-herbertenol and (-)-β-herbertenol, were also present in the extract of Herbertus dicramus. The structures of the new compounds were elucidated with the help of 1H, 13C NMR, two dimentional NMR and mass spectroscopy.